2016
DOI: 10.1007/s10750-016-2700-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexible prey handling, preference and a novel capture technique in invasive, sub-adult Chinese mitten crabs

Abstract: Eriocheir sinensis (Crustacea: Brachyura: Varunidae) is one of only two crabs on the world's list of 100 most invasive aquatic invertebrates. This crab has successfully invaded NE Europe as well as the United States, eastern Canada, southern Iraq and Tokyo Bay, Japan. In England, the River Thames population of E. sinensis continues to increase in numbers and disperse westward upstream, although little is known about foraging. The present study undertook a preference and prey handling study of sub-adult mitten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…obs. ; Mills et al 2016). In the field, strong predation pressure from E. sinensis whether prey are abundant (small h) or rare (large a) could lead to prey population decline or extinction.…”
Section: Discussionmentioning
confidence: 99%
“…obs. ; Mills et al 2016). In the field, strong predation pressure from E. sinensis whether prey are abundant (small h) or rare (large a) could lead to prey population decline or extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Outside its native range, E. sinensis is considered an invasive species that has successfully established breeding populations in Europe and North America (Brockerhoff and McLay, 2011;Dittel and Epifanio, 2009;Herborg et al, 2003). Previous studies have demonstrated the negative impacts of this invasive species in introduced regions, including predation on native species (Mills et al, 2016;Rosewarne et al, 2016;Rudnick and Resh, 2005;Webster et al, 2015;Wójcik et al, 2015), competition with native organisms (Gilbey et al, 2008;Zhang et al, 2019b), pathogen transmission (Schrimpf et al, 2014), and riverbank erosion (Dittel and Epifanio, 2009). Multiple introduction vectors are blamed for the transportation of E. sinensis into new habitats, including ballast water discharge, the live crab trade, and religious animal release practices (Cohen and Carlton, 1997;Dittel and Epifanio, 2009;Low et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When they feed on these hard-shelled preys, many crabs are capable of extracting the meat by peeling the shell aperture and thus avoid spending more time and energy in shell crushing (Rossi and Parisi, 1973). Besides this specialization, there are also reports of more generalized behavior in crab feeding, such as a widespread preference for feeding on small-size preys: these are presumably easier to manipulate and crush and hence offer higher net energy gains ( Juanes, 1992;Mills et al, 2016). It is therefore important to know the individual prey preference of crab predators in order to better understand their ecological effects on their prey populations and, as a result, on the assemblage composition of intertidal inhabitants.…”
Section: Introductionmentioning
confidence: 99%